Reconfigurable Agents for Heterogeneous Wireless Sensor Networks - Cemin, David; Götz, Marcelo; Pereira, Carlos Eduardo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
Heterogeneous wireless sensor networks combine static nodes and mobile nodes. These mobile nodes might present a more sophisticated and powerful computation platform if compared to static nodes. UAVs (Unmanned Aircraft Vehicle) can confer mobility feature to a node, as well as offer a powerful computation platform, including reconfigurable hardware as an execution platform alternative. These types of networks enable a vast and interesting spectrum of applications, like area surveillance, public security support, among others. An UAV might join or leave a network, and thereby migration of agents might occur among UAVs. In this scenario, this paper proposes a reconfigurable agent, which is able to be executed as pure software agent, as well as a hardware agent, depending on the available execution environment and application decisions. The proposed architecture for a reconfigurable agent presents the necessary transparency so that the rest of the system is not aware of the agents' nature. Moreover, the system enables a dynamic migration of an agent reconfiguring thereby itself to the target execution environment, in a transparent manner as well. Case studies and results are presented, showing the feasibility and costs related to the architecture proposed.